Riding the wave of genomics to investigate aquatic coliphage diversity and activity - Slawomir Michniewski; Tamsin Redgwell; Aurelija Grigonyte; Branko Rihtman; Maria Aguilo‐Ferretjans; Joseph Christie‐Oleza; Eleanor Jameson; David J. Scanlan; Andrew D. Millard (Environmental Microbiology, 2019)
Summary Bacteriophages infecting Escherichia coli (coliphages) have been used as a proxy for faecal matter and water quality from a variety of environments. However, the diversity of coliphages that is present in seawater remains largely unknown, with previous studies largely focusing on morphological diversity. Here, we isolated and characterized coliphages from three coastal locations in the United Kingdom and Poland. Comparative genomics and phylogenetic analysis of phage isolates facilitated the identification of putative new species within the genera Rb69virus and T5virus and a putative new genus within the subfamily Tunavirinae . Furthermore, genomic and proteomic analysis combined with host range analysis allowed the identification of a putative tail fibre that is likely responsible for the observed differences in host range of phages vB_Eco_mar003J3 and vB_Eco_mar004NP2.